The Leadership Role of School Principals in Curriculum Management: Systematic Literature Review Analysis - Nurlaeli, Acep; Ferianto, Ferianto; Makbul, M.; Munafiah, Nida’ul (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
The role of the principal in curriculum management is critical to ensure effective implementation and alignment with educational standards and objectives. This study aims to determine the role of principals in curriculum management based on a systematic review of the literature using NVivo software. This research uses the SLR method with an inductive approach, and the analysis is carried out using NVivo software. A literature review study using NVivo found that: 1) After screening with inclusion and exclusion criteria, the number of relevant articles was 21. The articles are spread across various journals, with the highest number being four articles in the journal "School Leadership and Management"; 2) Principals have diverse roles in curriculum management, with the terms leadership, principal, curriculum, transformation, management, and supervision being the main focus; 3) The role of the principal in curriculum management has intrinsic and extrinsic factors based on a literature review using NVivo software that shows the conclusion that the factors of the principal's role in curriculum management include leadership, decision making, and coordination. This research provides a deep understanding of the role of principals in curriculum management, which can be a foundation for the professional development of principals and the improvement of the education system. By understanding the role and factors that influence it, educational institutions can identify problems and find more effective solutions to improve the quality of education.